Mycotoxigenic Aspergillus flavus from ginger and turmeric consumed in the Niger Delta Region of Nigeria - M I Godwin-Egein, V C Okereke, (Journal of Spices and Aromatic Crops, 2019)
Ginger and turmeric sold in the open markets and retail outlets in southern Nigeria were sampled between April and August, 2017. This period coincided with the first bimodal peak of the rainy season of the 2017 cropping season. Malt extract agar (MEA) and Dichloran 18% glycerol (DG18) media were used to isolate fungi from samples with or without surface sterilisation. Aspergillus spp isolated were examined for the production of orange-yellow pigmentation and blue fluorescence on the reverse side of the plate on CAM under UV light. Aflatoxin production by Aspergillus flavus on yeast extract sucrose (YES) was verified quantitatively using High Performance Liquid Chromatography (HPLC). Data showed that Fusarium, Penicillium and Aspergillus spp were the dominant fungal flora. Toxigenic isolates of A. flavus; AFg1, AFg3, AFt1, and AFt3 produced both orange-yellow pigmentation and blue fluorescence on CAM. The production of AFB1 and AFB2 on YES medium was confirmed using HPLC. The occurrence of toxigenic fungi indicates that there is a potential risk of mycotoxin contamination in ginger and turmeric consumed in southern Nigeria and problems can arise from contamination with aflatoxins.